Students' Errors in Solving Algebraic Dominant Numeration Problems Based on Kastolan Theory - Suryani , Pitri; Nurrahmawati, Nurrahmawati; Afri, Lusi Eka; Arcat, Arcat (International Journal of Applied Learning and Research in Algebra, 2025)
Minimum competency assessment is a basic competency that all students need to be able to develop their own abilities and play an active role in society in positive activities. Minimum competency assessment aims to measure students' cognitive learning outcomes which include reading literacy and numeracy competencies. This study aims to determine the types of errors made by students in solving algebraic domain numeracy problems based on the kastolan theory, namely: (1) conceptual errors, (2) procedural errors, (3) technical errors. The research that has been conducted is a qualitative descriptive study with a research instrument of three AKM type algebra essay questions on 26 class VIII 3 students at SMP N 1 Tambusai. The results obtained based on the results of student answer sheets include: (1) conceptual errors of 30.76%, procedural errors of 38.46%, and technical errors of 32.05%. It can be concluded that the mistakes that students often make are procedural errors. The results of this study provide an overview of the various errors made by students in solving algebraic domain AKM problems, so that they can determine follow-up actions so that students' numeracy skills become better.